Correlation Analysis of Food Consumption Pattern that Induced Hypertension on Farmer in Rural Areas of Jember Regency - Ida Srisurani Wiji Astuti (Journal of Agromedicine and Medical Sciences, 2017)
Food consumption pattern has been suspected as a factor that cause hypertension, whereas other than that it may also induced by another life style. Farmers’ hypertension prevalence is growing up in rural areas. This fact shows that the activity of farm as heavy as how farmers facing their problem in daily live. The aim of the study is explaining how the food consumption pattern of farmers induced hypertension meanwhile they are living in the rural areas, as the firsthand customer of the fresh product from farming and agroindustry. An observational analytic study by using asymmetry association of lambda was conducted to prove the correlation between hypertensive pattern consumption and prevalence hypertension of farmers. One hundred respondents (from Mayang and Ledokombo districts) were given food frequency questionnaire. The results showed the food pattern with high level of cholesterol, dairy milk and the product of it and using high mono sodium glutamate,were having a significant level of p value (< 0,05). It means there are strong correlation between them to hypertension prevalence. Keywords: farmer, consumption pattern, hypertension